Common stroke mistakes in Chinese character writing among Business Administrative students / Ch’ng Looi-Chin, Ting Hie-Ling and Chuah Kee-Man - Ch’ng, Looi-Chin; Ting, Hie-Ling; Chuah, Kee-Man (Universiti Teknologi MARA, Cawangan Melaka, 2018)
Due to the diplomatic and economic relationship between Malaysia and China, many undergraduates are encouraged to enroll the Chinese course in their respective universities. Among those, students of Business Administration in UiTM Sarawak are made compulsory to join Mandarin course. This has made their learning an uphill challenge because the learning of Chinese character writing is viewed as one of the toughest elements in Chinese language course especially among non-Chinese due to lack in their learning environment to assist and support their learning. This study aims to identify the common stroke writing mistakes among the non-Chinese learners. A dictation of 68 words has been carried out to all 50 undergraduates who enrolled the Mandarin level 2 course. The test items in the dictation were the extracts of common words that they have learned and practiced in their course’ text book for a semester. Data suggested that Stroke Misalignment, Stroke’s Shape and Non-existing Strokes are the most common mistakes done among the non-Chinese learners. The findings suggest that the teaching of stroke order might be the most crucial component to help learners to rectify their stroke writing mistakes. However, further studies are needed to examine suitable teaching methods that can further assist learners to achieve accuracy in stroke writing.